2019
DOI: 10.12669/pjms.35.2.613
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants associated with parental knowledge of screening services for thalassemia major in Lahore

Abstract: Objective: To assess the sociodemographic factors affecting parental knowledge regarding availability of screening services for thalassemia major. Methods: A cross sectional study was conducted among biological parents of thalassemic children at three registered centers of blood transfusion in Lahore. A sample of 186 parents was selected through systematic random sampling. A pretested questionnaire was used to collect data. IRB clearance was obtained and informed consent was taken before data collection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Regarding to the relation between caregivers` knowledge, burnout and their demographic characteristics of studied, the results of the present study revealed that, there were a statistically significant relation between caregivers` total knowledge scores and their age, gender, level of education, marital status, occupation, place of residence, monthly income and number of family members. These results agreed with study performed by Manzoor & zakar [25], whose conduct study in Lahore (study sample equal 186 parents) and entitled as "Sociodemographic determinants associated with parental knowledge of screening services for thalassemia major in Lahore" who stated that, there were statistically significant relation between parents total knowledge and their gender, level of education, marital status, occupation and monthly income. Also, these results disagreed with study Performed by Williams [26], whose conduct study at mysore (study sample equal 60 caregivers) and entitled as "A study was to assess the knowledge of caregivers regarding thalassemia in selected hospital at mysore with a view to develop information booklet" who found that, there were no significant relation between total knowledge scores and their age, gender, level of education, marital status, occupation and monthly income.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding to the relation between caregivers` knowledge, burnout and their demographic characteristics of studied, the results of the present study revealed that, there were a statistically significant relation between caregivers` total knowledge scores and their age, gender, level of education, marital status, occupation, place of residence, monthly income and number of family members. These results agreed with study performed by Manzoor & zakar [25], whose conduct study in Lahore (study sample equal 186 parents) and entitled as "Sociodemographic determinants associated with parental knowledge of screening services for thalassemia major in Lahore" who stated that, there were statistically significant relation between parents total knowledge and their gender, level of education, marital status, occupation and monthly income. Also, these results disagreed with study Performed by Williams [26], whose conduct study at mysore (study sample equal 60 caregivers) and entitled as "A study was to assess the knowledge of caregivers regarding thalassemia in selected hospital at mysore with a view to develop information booklet" who found that, there were no significant relation between total knowledge scores and their age, gender, level of education, marital status, occupation and monthly income.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that about 91% parents had knowledge about screening services to be done before and throughout the pregnancy and 89% knew about genetic screening to be done before marriage. 3 Study done by Biswas et al also found that 52.4% of study subjects had heard about premarital counselling and 50.9% about antenatal screening. 4 The results of present study was similar to a study conducted Rao et al in 2004 for evaluation of psychopathology of parents having children with chronic illness and coping mechanisms used by them.…”
Section: Discussionmentioning
confidence: 88%
“…Similar findings were reported by studies from the same region. For example, Manzoor I, et al reported poor parental knowledge of screening services for thalassaemia major among mothers who were housewives, had a lower education level and had lower family income 23 . One important finding of our study is that having an accurate knowledge on HSCT was associated with a lower prevalence of hepatomegaly and splenomegaly.…”
Section: Discussionmentioning
confidence: 99%